The Effect of Parathyroidectomy on Insulin Sensitivity in Patients with Primary Hyperparathyroidism – an never Ending Story? - Cvijovic, G.; Micic, D.; Kendereski, A.; Milic, N.; Zoric, S.; Sumarac-Dumanovic, M.; Stamenkovic-Pejkovic, D.; Polovina, S.; Jeremic, D.; Gligic, A. (Experimental and Clinical Endocrinology & Diabetes, 2015)
Previous studies demonstrated insulin resistance and increased prevalence of impaired glucose tolerance and type 2 diabetes mellitus in patients with primary hyperparathyroidism (PHPT). The effect of curative parathyroidectomy on insulin sensitivity was associated with conflicting results depending on which method for measuring the insulin sensitivity has been used. There was no improvement using HOMA and QUICKI while minimal model demonstrated significant improvement in insulin sensitivity. The aim of our study was to evaluate the insulin sensitivity before and after parathyroidectomy in patients with PHPT using a euglycemic clamp. 44 patients with PHPT and 11 age and body mass index matched healthy controls participated in study protocol. Before surgery M values and HOMA IR suggest insulin resistance in patients with PHPT. There was no difference in M index (3.74±1.89 vs. 4.62±2.27, p>0.05), HOMA IR (2.94±1.39 vs. 3.29±0.81, p>0.05), AUC glucose (863.0±261.3 vs. 842.3±165.5, p>0.05), AUC insulin (7068.7±4159.0 vs. 7229.6±2581.7, p>0.05), ISI (4.73±2.77 vs. 4.25±2.94, p>0.05) and AIR (47.89±32.05 vs. 38.96±21.20, p>0.05) between patients with PHPT and HC. There was significant improvement in insulin sensitivity after parathyroidectomy but both preoperative and postoperative M values were not significantly different in comparison to HC. There were no significant changes in HOMA IR, AUC glucose, AUC insulin, ISI and AIR before and after therapy. In conclusion, we observed significant improvement in insulin sensitivity after parathyroidectomy in patients with PHPT. There was no difference in parameters of insulin secretion before and after parathyroidectomy in patients with PHPT.
Keywords: PTH; calcium; clamp; homa; ISI; surgery